2013
DOI: 10.3947/ic.2013.45.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal Carriage Rate and Serotypes ofStreptococcus pneumoniaeand Antimicrobial Susceptibility in Healthy Korean Children Younger than 5 Years Old: Focus on Influence of Pneumococcal Conjugate Vaccination

Abstract: BackgroundEven after pneumococcal vaccination introduction, Streptococcus pneumoniae (pneumoccocus) is still an important cause of respiratory and invasive severe infection. Pneumococcus is resided in nasal mucosa and local or systemic infection begins with the nasal mucosa damage. We studied the indirect effect of pneumococcal conjugate vaccine (PCV) on pneumococcal nasopharyngeal carriage rates, serotypes and antimicrobial susceptibility between vaccinate and non-vaccinated children.Materials and MethodsFrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
2
6
1
1
Order By: Relevance
“…The significant reduction in vaccine serotypes in nasopharyngeal colonization was consistent with findings from other post-PCV surveillance studies and reflects the effectiveness of immunization [12,13,[14][15][16][17]24,25]. Our surveillance was conducted in 2013-2014 which was around 18 months after introduction of PCV13 into the CIP.…”
Section: Tablesupporting
confidence: 88%
See 2 more Smart Citations
“…The significant reduction in vaccine serotypes in nasopharyngeal colonization was consistent with findings from other post-PCV surveillance studies and reflects the effectiveness of immunization [12,13,[14][15][16][17]24,25]. Our surveillance was conducted in 2013-2014 which was around 18 months after introduction of PCV13 into the CIP.…”
Section: Tablesupporting
confidence: 88%
“…Serotype replacement in pneumococcal carriage in these children was evident with the emergence of serogroup 15 and serotype 6C. Local prevalence of pneumococcal carriage as shown by our study was low when compared with data from other countries which show carriage rates of 28.8-35% in children under 2 years old [12,14,15,[23][24][25]. Previous local surveillance studies have also shown lower pneumococcal carriage rates than Caucasian and other Asian populations [12,14-17,23-26], which may explain the lower IPD burden in Hong Kong than other countries [27].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…In one hospital, among 842 hospitalized children with lower respiratory infections tested between 2009 and 2010, the pneumococci serotypes were determined using multiplex polymerase chain reaction tests, which reported among 167 specimens from which pneumococcal DNA was detected a predominance of serotypes 19A (23.4%), 6A/B (16.2%), 19F (11.4%), and 15A (5.4%) [63]. A hospital-based study reported that among pneumococci isolated from the nasopharynx of healthy children, 19F (13.9%) and 34 (11.4%) were the major serotypes among children with vaccination records, while 6A (15.5%) and 6D (12.1%) were the main serotypes identified among children with no vaccination records [64]. …”
Section: Serotype Changesmentioning
confidence: 99%
“…PCV7, serotypes included in 7-valent pneumococcal conjugate vaccine (4, 6B, 9V, 14, 18C, 19F, 23F); PCV10, serotypes included in 10-valent pneumococcal conjugate vaccine (4, 6B, 9V, 14, 18C, 19F, 23F, 1, 5, 7F); PCV13, serotypes included in 13-valent pneumococcal conjugate vaccine (4, 6B, 9V, 14, 18C, 19F, 23F, 1, 5, 7F, 3, 6A, 19A); NT, nontypable pneumococci. a Nontypable pneumococci were excluded from analysis in Cho et al [42], while Kim et al [62], Ahn et al[63], and Lee et al [64] included the nontypable pneumococci. b In the Cho et al1997-1998 and 2001-2002 study periods [42], differentiation of serotypes 6C/6D from 6A/6B was not carried out; in Ahn et al [63], differentiation between serotypes 6A and 6B was not carried out; in Lee et al [64], differentiation between serotypes 9A and 9V was not carried out; therefore only the estimated vaccine types are described.…”
Section: Figurementioning
confidence: 99%